User-Centered Design pada User Interface (UI) / User Experience (UX) Prototyping Aplikasi E-Commerce - Ronni Sahat Hutabarat; Ketut Sudaryana (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study develops an e-commerce application prototype with a User-Centered Design (UCD) approach that places user needs and preferences as the main focus. User interface (UI) and user experience (UX) design play an important role in creating intuitive interactions, which contribute to user satisfaction and retention. The UCD method allows testing and adjusting designs based on user feedback, thereby improving navigation comfort. The UCD stages in this study include planning, understanding the context, identifying user needs, creating design solutions, evaluating, and finalizing the design. The needs analysis revealed important features, such as digital product recording, displaying structured information through a dashboard, and a search feature. The developed prototype showed increased inventory management efficiency and reduced recording errors. The results of the study showed that the application of UCD in the development of the UI/UX e-commerce prototype created a user-friendly interface and improved the shopping experience. This application is expected to meet user expectations and support a comfortable and satisfying shopping experience, and emphasize the importance of user involvement in the product development process.